Bali Animal Welfare Association Sebagai Gerakan Sosial Baru Dalam Melestarikan Anjing Lokal Bali - Ari Wiadnyana, Sang Putu Agus; Kebayantini, Ni Luh Nyoman; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT Balinese dogs and Balinese people are two things that can’t be separated. Along with the development of the times, the dog race began to enter Bali. This phenomenon then makes the condition of local Bali dogs become marginalized and tend not to be noticed. This condition is the background of the formation of a dog rescue organization, the Bali Animal Welfare Association. Bali Animal Welfare Association is one of the animal rescue organizations in Bali. The existence of this organization is to provide education to the community to re-concern the condition and sustainability of local dogs Bali. Based on the phenomenon, the writer took the title of Bali Animal Welfare Association research as a New Social Movement in Bali Dog Conservation to understand the problem. This research uses Resource Mobilization Theory by Anthony Oberschall. In each program, Bali Animal Welfare Association seeks to invite the community to play an active role so as to foster community awareness of the preservation of local dogs Bali. While the influence of social movements undertaken by BAWA can be seen from the increasing public awareness to re-preserve the Bali dog and their participation in BAWA activities. Keywords: Bali local dog; Bali Animal Welfare Association; social movement; resource mobilization.